An equivalent model of corrugated panels with axial and bending coupling. (15th April 2017) - Wang, Chen; Khodaparast, Hamed Haddad; Friswell, Michael Ian; Shaw, Alexander David
Highlights: The axial and bending coupling of the corrugated panel is discussed in this paper. The coupling is a supplementary to the previous equivalent model when the corrugated panel has a fixed boundary condition. The analytical expressions of the coupling deflections are obtained and validated by numerical method. The method to eliminate the coupling is proposed together with its influence on the compliant structure. Abstract: In this paper, modification of an existing equivalent model of the corrugated panel is investigated. The axial and bending coupling of the corrugated panel supplements the previous equivalent properties when the corrugated panel has a fixed boundary condition. The analytical expressions of the coupling vertical deflections are obtained and verified by the finite element method. A method to eliminate the vertical deflection is proposed, and the importance of the coupling effect is demonstrated by the application of the modified model in a compliant structure.